Exploring the Practice of Ayurveda in the United Kingdom - The Ayurvedic Practitioners’ Perspective - Paragjee, Niyati (2009)
Background: The popularity and use of complementary and alternative medicine (CAM) is increasing on a national and global level. One such complementary and alternative system of medicine is Ayurveda. Although there is a growing literature base around why people may turn to CAM, there remains a lack of research into the backgrounds and opinions of individuals who provide these services; perhaps because CAM treatments are mainly available in the private sector Aim: To explore the practice of Ayurveda in the U.K., from the perspective of Ayurvedic practitioners. To systematically collect data regarding: demographic characteristics, their background to practice Ayurveda, and attitudes towards: the awareness and acceptance of Ayurveda; laws and regulation; safety of Ayurvedic herbal medication; support systems available; and the ‘business’ of practicing Ayurveda in the U.K. Research Design: An exploratory study, using descriptive and quantitative research methods. Methods: An online questionnaire was devised specifically for this study. Regardless of their experience or qualifications to practice, all individuals who identified themselves as Ayurvedic practitioners were invited to participate. Data was analysed using descriptive statistics, as this study was entirely exploratory in nature, no analytical tests were conducted. Results: A total of twenty one responses were obtained from this survey. A vast majority of the respondents were members of the Ayurvedic Practitioners Association; a voluntary steering group of Ayurvedic practitioners. The treatments that are offered in the U.K. under the umbrella of Ayurveda varied from health promotion- dietary and lifestyle advice, herbal medication and massage, to more specific Ayurvedic treatments, such as panchakarma. Respondents were enthusiastic towards the change that regulation would have on their professional development opportunities, increased stature in the eyes of allopathic medicine and support structures available to them. Conclusion: The increased interest in CAM can have significant implications on nursing practice and the nursing profession as a whole, especially in terms of research opportunities. Results from this exploratory survey provided a useful insight into the background and opinions of Ayurvedic practitioners in the U.K. However, further research is needed on this topic, perhaps that which utilises quantitative research methods to explore the factors which affect the practice of Ayurveda in greater detail. Research into what medical practitioners and policy makers feel with regard to Ayurveda, and CAM in general, would also be useful.